ANALISIS KESADARAN MASYARAKAT DALAM MITIGASI BENCANA TANAH LONGSOR DI DESA DAYAKAN KABUPATEN PONOROGO - Fendy Eko Hardiawan; Ardhana Januar Mahardhani (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
Abstract This study aims to determine public awareness in terms of 3 aspects namely Knowledge, Attitude, and Behavior in three stages of Disaster Mitigation, namely Pre-Disaster, Emergency Response, and Post-Disaster.. The method used in this study is descriptive qualitative with data collection techniques of observation, interviews, and documentation, data analysis using the Miles and Huberman model, data reduction, data display, and data conclusions. The results of this research show: 1) public awareness in pre-disaster disaster mitigation; 2) public awareness in disaster mitigation at the emergency response stage; 3) public awareness in post-disaster disaster mitigation.